(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
Functional analytic psychotherapy (FAP) is a therapeutic approach that addresses clients’ change through modifying contingencies of reinforcement of behavior that function to increase the likelihood that clients can access valued goals. This is done by differential reinforcement of clients’ behaviors and discrimination training, in which the behavioral improvements are shaped and naturally reinforced by the therapist. As therapies evolve and are readied for dissemination, it is often the case that therapy principles may be simplified and language made more appealing to those adopting new techniques. This article raises two issues of concern that have occurred as the dissem- ination of FAP has gained momentum. Although notions of basic science behind FAP include basic ideas of stimulus discrimination, responding, and differential reinforce- ment, these elementary terms have been recast as awareness, courage, and love. This article focuses on two problems that may result from the use of the term love as a proxy for differential and positive reinforcement. First, love is problematic because the use of the term brings with it a cultural history that can be confusing for both therapists and clients alike, creating ethical risks. Second, love as a proxy term for reinforcement is inadequate because it does not entail the complexities of differential reinforcement, shaping, and punishment with differential reinforcement of other responses in the context of the clinical setting.